2013
DOI: 10.1074/jbc.m113.473520
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelial Calcium Channel TRPV5 Is Regulated Differentially by Klotho and Sialidase

Abstract: Background:The epithelial Ca 2ϩ channel TRPV5 facilitates Ca 2ϩ reabsorption in the kidney and is regulated by sialidase and the hormone klotho. Results: Sialidase stimulates TRPV5 plasma membrane stabilization in a lipid raft-dependent manner, while klotho increased cell surface expression of the channel via its N-glycan. Conclusion: Klotho and sialidase regulate TRPV5 membrane stabilization in a different manner. Significance: Understanding the regulation of TRPV5 is crucial to treat patients with Ca 2ϩ -rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…Klotho has previously been shown to affect a variety of further channels, such as the epithelial Ca 2+ channels TRPV5 [62,63,64,65,66] and TRPV6 [66], as well as the K + channels ROMK [24,62], KCNQ1/KCNE1 [67] and hERG [68]. Klotho apparently does not appreciably affect the channels TRPV4 [66] or TRPM6 [66].…”
Section: Discussionmentioning
confidence: 99%
“…Klotho has previously been shown to affect a variety of further channels, such as the epithelial Ca 2+ channels TRPV5 [62,63,64,65,66] and TRPV6 [66], as well as the K + channels ROMK [24,62], KCNQ1/KCNE1 [67] and hERG [68]. Klotho apparently does not appreciably affect the channels TRPV4 [66] or TRPM6 [66].…”
Section: Discussionmentioning
confidence: 99%
“…The reversal of the effect of Klotho indicates that the effect of Klotho on Slc6A8 indeed requires β-glucuronidase activity of Klotho. Previous studies suggested that Klotho may regulate ion channels by removing terminal sialic acids [5,6]. …”
Section: Discussionmentioning
confidence: 99%
“…The extracellular domain of the Klotho protein may function as enzyme with β-glucuronidase activity and, after being cleaved off, as hormone [3,4,5,6,7]. Klotho expression is a decisive determinant of ageing and life span [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular domain of the Klotho protein may be cleaved off and function as enzyme with β-glucuronidase activity [3,4,5,6,7]. Klotho has a powerful impact on aging and life span [8,9].…”
Section: Introductionmentioning
confidence: 99%